2020
DOI: 10.1186/s12906-020-03021-3
|View full text |Cite
|
Sign up to set email alerts
|

A hospital-based study on complementary and alternative medicine use among diabetes patients in Rajshahi, Bangladesh

Abstract: Background: The use of complementary and alternative medicine (CAM) among type 2 diabetes mellitus (T2DM) patients is increasing worldwide. It can affect optimum glycemic management. This study was to determine the rate and influencing factors of CAM use among diabetes patients as well as their effect on glycemic control. Methods: This cross-sectional study was conducted among T2DM patients attending the outpatient department of Rajshahi Medical College Hospital. It is a tertiary hospital in the northern part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…Moreover, the most prevalent reasons for CAM use were a few side effects, improved efficacy, and that CAM is less expensive and more readily available. These causes are comparable to the findings of earlier investigations [ 11 , 17 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, the most prevalent reasons for CAM use were a few side effects, improved efficacy, and that CAM is less expensive and more readily available. These causes are comparable to the findings of earlier investigations [ 11 , 17 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, one-third of the participants had utilized CAM to manage chronic diseases at some point in their lives. This result is similar to what was previously reported among diabetic patients in Bangladesh (35.2%) [ 11 ]. A study in Malaysia found that 63.9% of patients with chronic conditions used CAM, and another study in North-India found the rate was 53.2%, which is significantly higher than our estimate [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to a recent survey, 32.8% of patients with chronic disease used some form of CAM for their chronic disease management in Bangladesh [15]. Another recent study from Bangladesh reported that 33% of diabetic patients in the northern part of the country used some different types of CAM to manage or treat their condition [16].…”
Section: Introductionmentioning
confidence: 99%